2018
DOI: 10.3390/land7020071
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Land and Vegetation Cover of Abandoned Fire Hazardous and Rewetted Peatlands: Comparing Different Multispectral Satellite Data

Abstract: Since the 1990s, many peatlands that were drained for peat extraction and agriculture in Russia have been abandoned with high CO 2 emissions and frequent fires, such as the enormous fires around Moscow in 2010. The fire hazard in these peatlands can be reduced through peatland rewetting and wetland restoration, so monitoring peatland status is essential. However, large expanses, poor accessibility, and fast plant succession pose as challenges for monitoring these areas without satellite images. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Additionally, if climate change leads to increasing occurrence of severe droughts (Dai, 2013; Jolly et al, 2015), the risk of releasing great amounts of C to the atmosphere in forest and peat fires increases. Peatland fires are already common in continental areas, for example, in many parts of Canada (Turetsky et al, 2004) and Russia (Sirin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, if climate change leads to increasing occurrence of severe droughts (Dai, 2013; Jolly et al, 2015), the risk of releasing great amounts of C to the atmosphere in forest and peat fires increases. Peatland fires are already common in continental areas, for example, in many parts of Canada (Turetsky et al, 2004) and Russia (Sirin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, increased lightning strikes will increase fire risk in Alaska (Veraverbeke et al 2017) but also northern Europe (Púčik et al, 2017). Fifth, the interaction between climatedriven changes in fire regimes and permafrost will compel a decrease in and a northern migration of Siberian taiga, which will result in the transition of tundra to taiga in northern Siberia (Tchebakova et al, 2009(Tchebakova et al, , 2011Sizov et al, 2021). Permafrost is not predicted to thaw deep enough to sustain dark-needled taiga (Pinus sibirica, Abies sibirica, and Picea obovata); nonetheless light-needled coniferous Larix is predicted to continue to dominate in eastern Siberia, maintaining a higher fire risk according to the Russian fire hazard rankings (Melekhov, 1980).…”
Section: Climate Change and Future Firesmentioning
confidence: 99%
“…The assessment of wildfire effects and post-fire regeneration using remote sensing has been done through the calculation of spectral vegetation indices [28]. These indices are calculated using the electromagnetic wave reflectance data of vegetation using passive sensors [29]. Several studies have successfully developed and applied vegetation indices (e.g., the Normalized Difference Vegetation Index, NDVI; the Composite Burn Index, CBI; the Differenced Normalized Burn Ratio, DNBR, and the Visible Atmospherically Resistant Index, VARI [24].…”
Section: Introductionmentioning
confidence: 99%
“…Bhagat et al [26] reported that UAVs provide data at fine resolution with the desired temporal resolution, which make them cost-effective and efficient data collectors. Regarding satellite images, Sirin et al [29] was able to compare different multispectral satellite data to assess vegetation cover in abandoned lands and rewetted peatlands. Bright et al [30] analyzed post-wildfire recovery in different coniferous forest types in North America using the Normalized Burn Ratio (NBR) derived from LandTrendr images.…”
Section: Introductionmentioning
confidence: 99%